1970
DOI: 10.1103/physrevc.2.2001
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Widths of Bound Nuclear Levels in the Vicinity of the Neutron Threshold

Abstract: The radiation widths of bound nuclear levels excited by (y, y') reactions in nuclei '39La, '3 Te, Sn, 6Sr, Se, and 6Zn have been measured. The present results together with results published by other authors using (y, y') reactions are summarized and compared with similar results obtained in capture reactions of thermal and resonance neutrons. The expected properties of the nuclear levels obtained by extrapolation of the giant-dipole resonance to lower energies are compared with the present experimental data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…In earlier NRF studies of 80 Se, the deexcitation of a level at 7820 keV was investigated [40,41]. In the present work, we could not confirm transitions depopulating a 7820 keV level, but we newly identified 180 γ rays up to 9.6 MeV in 80 Se.…”
Section: Introductioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In earlier NRF studies of 80 Se, the deexcitation of a level at 7820 keV was investigated [40,41]. In the present work, we could not confirm transitions depopulating a 7820 keV level, but we newly identified 180 γ rays up to 9.6 MeV in 80 Se.…”
Section: Introductioncontrasting
confidence: 46%
“…First, a spectrum of the ambient background adjusted to the intensities of the transitions from 40 K and 208 Tl decay in the in-beam spectrum was subtracted from the measured spectrum. To correct the spectrum for the detector response, spectra of monoenergetic γ rays were calculated in steps of 10 keV by using the simulation code GEANT4.…”
Section: E Determination Of Photoabsorption Cross Sectionmentioning
confidence: 99%
“…The resonance level at 8.995 MeV in Sm was first attributed to 15~ [9,10] but later studies showed that it in fact belonged to 144Sm [11]. The studies on these nuclei reported in Ref.…”
Section: Introductionmentioning
confidence: 96%
“…These nuclei have also been studied by the (7, Y') reaction, using nickel and lead capture 7 ray sources to excite corresponding resonant levels [8][9][10]. The resonance level at 8.995 MeV in Sm was first attributed to 15~ [9,10] but later studies showed that it in fact belonged to 144Sm [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation